Potassium hydrogen sulfate: An efficient catalyst in organic reactions - Baghernejad, Bita (European Journal of Chemistry, 2012)
Potassium hydrogen sulfate, KHSO4, has been used in many organic preparations as a good solid catalyst. The KHSO4 has received considerable attention since it is an inexpensive, eco-friendly, highly reactive, easy to handle and non-toxic catalyst for various organic transformations, affording the corresponding products in excellent yields with high selectivity. We wish to report some applications of this catalyst in organic reactions.